Pengaruh Kualitas Pelayanan Harga dan Lokasi Terhadap Kepuasan Pelanggan Harfia Hygienic Laundry di Wilayah Jakarta Pusat - Noviherni; Surya Dewantoro, Ispanji (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To analyze and determine the effect of Service Quality, Price and Location on Customer Satisfaction of Harfia Hygienic Laundry in Central Jakarta. Background Problems: The progress of the business world continues to progress rapidly along with the changing times and increasingly stringent living needs, this has resulted in the emergence of various types of new businesses from small to large scale, pioneered by the community. Novelty: Retesting the same variables by previous researchers, with different research objects and subjects. Research Methods: The technique used in sampling is saturation sampling, data analysis using the help of smart PLS version 4.0. Findings/Results: There is an effect of Service Quality on Customer Satisfaction, then there is an effect of Price on Customer Satisfaction, then there is no effect and no significant Location on Customer Satisfaction of Harfia Hygienic Laundry in Central Jakarta. Conclusion: The better the Service Quality in a company, the more it can increase the company's Customer Satisfaction. Prices that are in accordance with the quality of service offered and also prices that are affordable for customers can increase the company's customer satisfaction. An easily accessible location cannot determine the results of the company's customer satisfaction.